A relação das mulheres com a justiça e o direito: comarca das Alagoas – Capitania de Pernambuco (1712-1798) - Mendonça, Anne Karolline Campos (2017)
The research on the female presence in the Region of Alagoas was visualized, in this work, from the relations developed with the execution and conception of justice and the application of the law. Within this line of reasoning it is added that the present work proposes to observe this relationship within a reality lived in the eighteenth century in the jurisdiction of the villages south of the Captaincy of Pernambuco. It seeks to see not only possibilities, but also limitations that female historical agents found when engaging in lawsuits within the referred geographic and temporal framework. Analyzes under these perspectives are demonstrative of the social functions that women had in the development of Portuguese America and in the maintenance of the Portuguese monarchy. These objectives were synchronized with the validity of a legal status that provided the reaffirmation of the woman in a position considered inferior or not very dignified. These perceptions directed the work to the visualization of the possibilities and limits that the legal text and the notions of justice offered for the women who have been involved or have been involved in litigation. Women will be considered here in addition to the informal powers found mainly in the family and sexual environment. Another important point to emphasize is that the survey will bring cases of women from different social positions.